Significance of the climate and energy package for the development of renewable energy sources in the European Union - Agnieszka Pach-Gurgul (Comparative Economic Research. Central and Eastern Europe, 2014)
The utilisation of renewable energy in the European Union seems, at the present stage of energy policy development, inevitable. It offers many benefits, including, above all: the possibility of increasing the energy security of a given state or region thanks to the diversification of the sources of energy supply, the limitation of imports from energy suppliers, such as of natural gas or oil, thus reducing dependence on imported fossil fuels, ecological effects connected with the elimination of greenhouse gas emissions and other substances harmful to the natural environment, economic and social benefits, such as the creation of new jobs. The Climate and Energy Package obliges member states to pursue a common aim - to increase the share of renewable energy to 20% in the general energy balance of the European Union by 2020. This is a challenging task, since the renewable energy sector requires significant financial support to increase its competitiveness, compared to traditional energy sources. When adopting the Energy Package, leaders of member states did not anticipate the economic crisis and its impact on the European Union's economy, and on the energy sector in particular.
Keywords: 330; climate and energy package; renewable energy sources; European Union policy; energy security; energy mix; instruments for supporting development of RES